Analisis Pembiayaan Qardhul Hasan Pelaku UMKM Pada BMT Anugrah Tembung - Melisa, Melisa (Jurnal Ekonomi dan Keuangan Syariah, 2022)
This study aims to determine the efforts to empower Micro, Small and Medium Enterprises (UMKM) through Baitul Maal Wat Tamwil (BMT). This research is expected to provide accurate data regarding the empowerment of UMKM through the Qardhul Hasan contract in Batang Kuis, Tembung. This research is a qualitative research using data collection techniques through observation, documentation, and in-depth interviews. The data analysis technique used is descriptive qualitative. This research was conducted in Batang Kuis, Tembung. The subject of this research is BMT ANUGRAH Tembung. The result of this research is that the form of borrowing through Qardhul Hasan has the potential to be a source of substantial funds if it is utilized and managed optimally and its implementation is very useful for the community. Baitul Mal Wat Tamwil or BMT is an alternative solution in overcoming the problem of UMKM financing. The presence of BMT helps UMKM who cannot access financing facilities to formal financial institutions. In the implementation of the BMT Islamic Financial Institution, there are various ways of raising funds and ways of distributing funds. Fundraising is done through wadi'ah deposits and deposits. While the distribution of funds is done by financing murabahah, mudharabah, musyarakah, rahn (gada), ijarah, and qardhul hasan financing. Qardhul Hasan financing is the orientation of the function of the Islamic Financial Institution (Baitul Maal Wat Tamwil) as a social institution. Qardhul Hasan is a soft loan that is given on the basis of social obligations only. In this case the borrower is not required to return anything except the amount he borrowed.